Pendampingan Penyusunan Laporan Keuangan berbasis SAK EMKM pada UMKM Mama-Mama Papua di Kabupaten Sorong - Munzir, Munzir; Anwar, Vebby; Henraman, Henraman; Budi, Rosdinaman; Mikir, Soleman; Katumlas, Mina Marsela (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The purpose of this community service activity is to provide understanding and knowledge to MSME Mama-mama Papua, Malasom Village in preparing financial reports based on SAK EMKM so that they understand and are able to implement proper financial reporting. This assistance was carried out on September 12, 2024 through counseling and training activities. The results of this community service activity are an increase in the understanding and skills of participants in making financial reports based on SAK EMKM. By looking at the results of the pre-test and post-test produced with a level of 47% to 76%. This is an ongoing evaluation carried out by the community service team so that the understanding of MSME Mama-mama Papua continues to increase continuously.